Work, Wealth, and Postmodernism The Intellectual Conflict at the Heart of Business Endeavour - Bowden, Bradley (Springer International Publishing, 2018)
This work examines the rise of postmodernism in management scholarship and argues that the prevalence of postmodernist thought reflects a lack of understanding by management researchers of the core principles upon which Western business endeavour is based. The author highlights postmodernism's methodological and conceptual failings, such as disbelief in material progress and economic advancement, and its denial of generalizable laws to direct management research. In its place, the author proposes a return to traditional modernist principles in management research, based on scientific evidence. This ground breaking, timely work will spark debate and challenge previously accepted claims of postmodernism, a nice retort to the anti-business/anti-capitalist literature now prevalent in academia.